PEMBANGUNAN FASILITAS TOILET DAN RUANG GANTI DI KOLAM PEMANDIAN AIKDEWA, PRINGGASELA, LOMBOK TIMUR - Darayani, Dhiafah Hera; Makrifa, Auliya Isti; Prasetiawan, Jauhari; Lutfi, Lutfi; Sayfuddin, Sayfuddin; Firmansyah, Firmansyah; Wibisana, Bayu; Purnomo, Hendri; Ariyanti, Feni (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
Aikdewa Bathing Pool, located in Pringgasela Village, has great potential to become an attractive tourist destination in East Lombok. One of the much-needed facilities is clean and comfortable toilets and changing rooms. The condition of the toilets and changing rooms at Aikdewa Bathing Pool is very concerning. The existing facilities are only made of spandex and are not well maintained. Seeing the condition of Aikdewa bathing pool which is increasingly in demand by visitors, the author together with VLOK Foundation Holland took the initiative to improve the quality of facilities at the place. The steps carried out for the toilet and changing room facilities development program are divided into 3 stages, namely: the preparation stage, the implementation stage, and the post-development stage. The toilet and changing room facilities construction program at Aikdewa Bathing Pool has successfully built 2 toilet units and 1 changing room unit. The construction time is 1 month. The construction program of toilet and changing room facilities at Aikdewa Bathing Pool has successfully achieved the set targets.Aikdewa Bathing Pool, located in Pringgasela Village, has great potential to become an attractive tourist destination in East Lombok. One of the much-needed facilities is clean and comfortable toilets and changing rooms. The condition of the toilets and changing rooms at Aikdewa Bathing Pool is very concerning. The existing facilities are only made of spandex and are not well maintained. Seeing the condition of Aikdewa bathing pool which is increasingly in demand by visitors, the author together with VLOK Foundation Holland took the initiative to improve the quality of facilities at the place. The steps carried out for the toilet and changing room facilities development program are divided into 3 stages, namely: the preparation stage, the implementation stage, and the post-development stage. The toilet and changing room facilities construction program at Aikdewa Bathing Pool has successfully built 2 toilet units and 1 changing room unit. The construction time is 1 month. The construction program of toilet and changing room facilities at Aikdewa Bathing Pool has successfully achieved the set targets.